Research Mapping on the use of AI in Business Development - Judijanto, Loso; Lasmiatun, KMT; Rasidun , La Ode (West Science Journal Economic and Entrepreneurship, 2025)
Artificial Intelligence (AI) has emerged as a transformative force in business development, driving innovation, strategic decision-making, and digital transformation. This study conducts a bibliometric analysis using Scopus data and VOSviewer to map the research landscape on AI applications in business. The analysis reveals that AI is closely linked to innovation, big data, machine learning, sustainability, and competition, highlighting its broad impact across industries. The co-authorship and country collaboration networks indicate that research is concentrated in technologically advanced regions, with limited representation from developing economies, suggesting the need for more inclusive global research efforts. The findings also identify a fragmented research landscape, where multiple disciplines study AI’s role in business from diverse perspectives, reinforcing the need for greater interdisciplinary collaboration. Future research should focus on bridging regional gaps, exploring AI’s long-term effects on business sustainability, and integrating ethical considerations into AI-driven strategies. This study provides valuable insights for academics, policymakers, and business leaders, contributing to a comprehensive understanding of how AI is shaping modern business practices.